Effect of resistant starch type 4 addition on the in vivo and invitro glycemic index of Turkish noodle - Toptaş Bıyıklı, Ezgi; Kebapçılar, Levent; Karabudak, Efsun (Progress in Nutrition, 2022)
Background: Resistant starch (RS) is known to improve glucose tolerance and its intake with foods is low. The objective of the study is to enriching Turkish noodles with type 4 RS and determine the effect on the glycemic index (GI). Methods: After preliminary trials and sensory analyses, noodle formulations including 20% and 35% RS were determined and the noodles were produced accordingly. Reference foods (white bread, glucose) and noodles were used in GI test conducted on 15 healthy women. The participants consumed 25 g available carbohydrate amounts of food once a week for 11 weeks. The available carbohydrate amounts of the noodles with RS were calculated in two different ways and two different GI tests were performed for each. The noodle group for which the RS is evaluated in the total dietary fiber is called “TDF” and the noodle group for which it is evaluated in available carbohydrate amount is called “AC”. Blood glucose values were measured before consumption and at 15, 30, 45, 60, 90 and 120 min postprandially. GI values ​​were determined by calculating the incremental area under the curve (IAUC). Results: It was determined that the RS noodles in the AC group and the control noodles had low GI. [control noodles: 54.8, noodles with 20% RS(AC): 51.8, noodles with 35% RS(AC): 49.1] As the RS amount increased in the AC group, GI decreased (p<0.05). In vitro GI values were found to be similar to in vivo GI values in the AC group. Conclusions: The addition of type 4 RS reduced the glycemic response of Turkish noodles. The studies examining the effect of RS types on glycemic response should be increased.